Commodification of Conflict News: Political Economy of Syrian Conflict in Online News Media - M Fikri AR (Indonesian Student Association Study Center in Türkiye, 2024)
In the context of conflict, the responsibility to educate the public is not only in the hands of the government but also in the media institutions. Quality and objective media reports significantly contribute to increasing public literacy and knowledge. The problem is that news about conflict in online news media often emphasizes conflict controversy and the sadness of victims, but is incomplete and too short in explaining the conflict events that occurred. This research aims to reveal how the commodification of reporting on the Syrian conflict emerged and developed in online news media. This research data comes from online news published by hürriyet.com.tr as online news media. Data analysis was carried out using thematic analysis within the framework of a media political economy study which looks at the relationship between new media and conflict, the characteristics of news in online news media, as well as the tendency for the commodification of conflict news which can give negative impact on society in the long term. The results of the study show that in reporting on the Syrian conflict, economic interests are more prominent than the application of journalism principles which should be complete, this can be seen from the shortness of the news presented and the conflict that occurred is not presented holistically.